The comparative cost of food and beverages at remote Indigenous communities, Northern Territory, Australia. (22nd April 2015) - Ferguson, Megan; O'Dea, Kerin; Chatfield, Mark; Moodie, Marjory; Altman, Jon; Brimblecombe, Julie
Abstract: Objective: To determine the average price difference between foods and beverages in remote Indigenous community stores and capital city supermarkets and explore differences across products. Methods: A cross‐sectional survey compared prices derived from point‐of‐sale data in 20 remote Northern Territory stores with supermarkets in capital cities of the Northern Territory and South Australia for groceries commonly purchased in remote stores. Average price differences for products, supply categories and food groups were examined. Results: The 443 products examined represented 63% of food and beverage expenditure in remote stores. Remote products were, on average, 60% and 68% more expensive than advertised prices for Darwin and Adelaide supermarkets, respectively. The average price difference for fresh products was half that of packaged groceries for Darwin supermarkets and more than 50% for food groups that contributed most to purchasing. Conclusions: Strategies employed by manufacturers and supermarkets, such as promotional pricing, and supermarkets' generic products lead to lower prices. These opportunities are not equally available to remote customers and are a major driver of price disparity. Implications: Food affordability for already disadvantaged residents of remote communities could be improved by policies targeted at manufacturers, wholesalers and/or major supermarket chains.